Blind joint equalization of multiple synchronous mobile users using oversampling and/or multiple antennas - Slock, D.T.M. (Proceedings of 1994 28th Asilomar Conference on Signals, Systems and Computers, 1994)
We consider multiple (p) users that operate on the same carrier frequency and use the same linear digital modulation format. We consider m>p antennas receiving mixtures of these signals through multipath propagation (equivalently, oversampling of the received signals of a smaller number of antenna signals could be used). We consider conditions on the matrix channel response for the existence of a zero-forcing equalizer (ZFE) (which cancels intersymbol and inter-user interference). In the noise free case, we show how a ZFE can be obtained from linear prediction and the channel matrix itself can also be determined as a byproduct. The problem is one of signal and noise subspaces and we show a convenient way of solving the deterministic maximum likelihood problem using a minimal linear parameterization of the noise subspace. This parameterization is found as a byproduct in the linear prediction problem.< >